LncRNA NEAT1_1 suppresses tumor‐like biologic behaviors of fibroblast‐like synoviocytes by targeting the miR‐221‐3p/uPAR axis in rheumatoid arthritis. Issue 3 (12th July 2021) - Wang, Manli; Chen, Yixiong; Bi, Xuan; Luo, Xiqing; Hu, Zuoyu; Liu, Yan; Shi, Xiaoyi; Weng, Weizhen; Mo, Biyao; Lu, Yan; Pan, Yunfeng
Abstract: Fibroblast‐like synoviocytes (FLSs) are the predominant effector cells in the pathological progression of rheumatoid arthritis (RA). Therefore, elucidating the underlying molecular mechanism of the biologic behaviors in RA‐FLSs will be helpful in developing the potent targets for the treatment of RA. We have previously documented that the tumor‐like biologic behaviors of RA‐FLSs are exacerbated by urokinase‐type plasminogen activator receptor (uPAR), a specifically up‐regulated receptor in RA‐FLSs. Here, we investigate the further mechanism of uPAR and clarify its function in RA‐FLSs. We demonstrate that miR‐221‐3p positively correlates to uPAR and regulates uPAR level in RA‐FLSs. Simultaneously, one long noncoding RNA, nuclear paraspeckle assembly transcript 1_1 (NEAT1_1) is identified, which can predictively target miR‐221‐3p at three sites, indicating a strong possibility of being a competing endogenous RNA in RA‐FLSs. Interestingly, NEAT1_1 and miR‐221‐3p can colocate in the nucleus and cytoplasm in RA‐FLSs. Importantly, NEAT1_1 can act as a rheostat for the miR‐221‐3p/uPAR axis and the downstream JAK signaling. In line with the biologic function, NEAT1_1 negatively regulates the tumor‐like characters, and cytokine secretions of RA‐FLSs. Collectively, our data provide new insight into the mechanisms of NEAT1_1 in modulating RA‐FLSs tumor‐like behaviors. The targeting of NEAT1_1 and miR‐221‐3p/uPAR axis may have a promising therapeutic role in patients with RA. Graphical Abstract: Urokinase‐type plasminogen activator receptor and the function of nuclear paraspeckle assembly transcript 1 _1 in regulating rheumatoid arthritis fibroblast‐like synoviocytes.